BEBERAPA ASPEK YANG BERKAITAN DENGAN KEJAHATAN TERHADAP KEMANUSIAAN (CRIMES AGAINST HUMANITY) DALAM PERSPEKTIF HUKUM INTERNASIONAL - Ayu Nrangwesti (Hukum Pidana dan Pembangunan Hukum, 2021)
Crimes against humanity are crimes that are classified as delict jure gentium, which have been in the spotlight since the trial of criminals from World War II. Because of the word humanity contained in it, this crime is difficult to understand because it has an abstract and broad value. The Study of crimes against humanity viewed from several aspect of international law.is a way to better understand these crimes. Crimes against humanity in the Rome Statute 1998 are regulated in Article 7. This article describes spesifically the forms ofcrimes agains humanity and their elements. Article 7 places a limit on the act of giving rise to this crime, only for an attack toward civilian population by a state authority. The aspect of universal jurisdiction is the hallmark of crimes against humanity. The universal principle does not pay attention to the area where the crime occurs and does not pay attention to nationality whether is passive or active. Law enforcement for trial and punishment to the perpetrators of this crime is carried out by the International Criminal Court on the basis of state compliance through state consent by ratification and other legally binding methods to the Rome Statute 1998. The state’s obligation to take preventive measures so that crimes do not occur and also prosecuting and punishing the perpetrators can be build as a model of state responsibility. The occurrence of the crimes in the state territorial sovereignity might allows humanitarian intervention by other states based on the doctrine of responsibility to protect, but with 2 (two) main and strict condition only, namely state unwilling and unable, and legalized by the UN Security Council.Key Words: Crimes Against Humanity, Rome Statute 1998, Universal Jurisdiction, Responsibility to Protect, State Compliance, State Obligation.